The extent of sorbent attrition and degradation of ethanol-treated CaO sorbents for CO2 capture within a fluidised bed reactor - Clough, Peter T.; Greco, Gianluca; Erans, María; Coppola, Antonio; Montagnaro, Fabio; Anthony, Edward J. (Elsevier, 2017)
The application of an ethanol pre-treatment step on biomass-templated calcium looping sorbents resulting in an improved pore structure for cyclic CO2 capture was investigated. Three ethanol solutions of varying concentrations were used with an improved pore and particle structure, and thermogravimetric analyser CO2 carrying capacity arising with the 70 vol% ethanol solution. The extent of attrition of these sorbents was tested within a fluidised bed reactor and compared against an untreated sorbent and a limestone base case. It found that despite the ethanol-treated sorbents displaying an admirable CO2 carrying capacity within the thermogravimetric analyser even under realistic post-combustion conditions, this was not translated equivalently in the fluidised bed. Attrition and elutriation of the biomass-templated sorbents was a significant issue and the ethanol pre-treatment step appeared to worsen the situation due to the roughened surface and mechanically weaker structure.
Keywords: Ethanol pre-treatment; Attrition; Fluidised bed; Calcium looping; CCS